Multidimensional federalism: A revision of the two-tier federal structure as seen through the Canada Works Infrastructure Program. - Morrison, Jeff. (University of Ottawa (Canada), 1996)
Conventional theories of Canadian federalism revolve around the notion of dualism--the federal system is comprised of two levels of government; the national and provincial governments. This thesis argues that due to the changing nature of the Canadian political landscape, a more realistic interpretation of the federal model is that of multidimensional federalism, a model which allows for other orders of government to be included within the federal system. Currently, these other orders of government include municipalities, regional governments, school boards, and aboriginal governments. This paper examines from a theoretical standpoint why the conventional model of federalism no longer provides an accurate representative model, and why the multidimensional model is a more realistic interpretation. It then examines the legitimacy behind the inclusion of the four additional factors within the federal system. Finally, the Canada Works Infrastructure Program is used as a case study of multidimensional federalism in operation.
Keywords: Canadian Studies.